New Trend of Space-Frequency Block Code-OFDM - Al-Qaradaghi, Thuraya M.; Hussein, Refat Talib (Sulaimani Journal for Pure and Applied Sciences, 2010)
To avoid the problem of fast channel variations in time, the symbols of an orthogonal design can be transmitted on neighboring subcarriers of the same Orthogonal Frequency Division Multiplexing (OFDM) symbol rather than on the same subcarrier of the subsequent OFDM symbols. This also reduces the transmission delay. Space-Frequency Block Codes (SFBC) avoids the problem of fast time variations. A new trend of SFBC introduced and examined for flat and frequency-selective channels over various values of Doppler frequencies and various type of modulation (QPSK, 8-PSK, 16-QAM and 32-QAM). Alamouti code was applied to a block of the odd and even elements instead of one symbol. The performance comparisons of bit error probability for the conventional SFBC-OFDM and the proposed one have been presented. As a result, it can be concluded that the proposed structure achieves much lower bit error rates. MATLAB version 7.4 had been used as a simulation tool.
Keywords: STC; SFBC; OFDM